2015
DOI: 10.1016/j.clim.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Applying complement therapeutics to rare diseases

Abstract: Around 350 million people worldwide suffer from rare diseases. These may have a genetic, infectious, or autoimmune basis, and several include an inflammatory component. Launching of effective treatments can be very challenging when there is a low disease prevalence and limited scientific insights into the disease mechanisms. As a key trigger of inflammatory processes, complement has been associated with a variety of diseases and has become an attractive therapeutic target for conditions involving inflammation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 137 publications
0
61
0
Order By: Relevance
“…For example, immune complexes present in systemic lupus erythematosus (SLE) cause consumption of complement components in the circulation and deposition of complement activation products in the kidney (lupus nephritis) and other organs 92 . Similar mechanisms are involved in antiphospholipid antibody syndrome, myasthenia gravis, and many other autoimmune diseases 3,92 . In patients with ANCA-associated vasculitis, neutrophil priming by C5a or other stimuli leads to the expression of proteins that are recognized by autoantibodies.…”
Section: Complex Involvement In Clinical Disordersmentioning
confidence: 86%
See 2 more Smart Citations
“…For example, immune complexes present in systemic lupus erythematosus (SLE) cause consumption of complement components in the circulation and deposition of complement activation products in the kidney (lupus nephritis) and other organs 92 . Similar mechanisms are involved in antiphospholipid antibody syndrome, myasthenia gravis, and many other autoimmune diseases 3,92 . In patients with ANCA-associated vasculitis, neutrophil priming by C5a or other stimuli leads to the expression of proteins that are recognized by autoantibodies.…”
Section: Complex Involvement In Clinical Disordersmentioning
confidence: 86%
“…Although this effect was most obvious for older cellulose-based haemodialysis filters, modern synthetic filters with improved biocompatibility still induce substantial complement activation through all initiation pathways 3,147 . The generation of C5a during haemodialysis-induced complement activation is associated with neutrophil activation and an increase in TF expression as a primary initiator of coagulation.…”
Section: Complement-mediated Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Among strategies aimed at intercepting C3, derivatives of the compstatin family and soluble CR1 displayed favorable effects in preclinical models and in patients with age-related macular degeneration or C3 glomerulopathy585960. However, targeted C3 inhibition often raised the concern that a completely shut down of C3 activity could increase susceptibility to infections.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to alternative drivers of disease pathology, or unfavourable pharmacological characteristics of antibody-based inhibition of C5. Clinical trials of another monoclonal C5 inhibitor, LFG316, has reported a similar lack of effect in the treatment of macular degeneration (Reis et al 2015). In contrast, the C5 inhibitor, Zimura, has reported benefits in clinical trials for the treatment of age-related macular degeneration, with phase II/III trials for geographic atrophy and macular degeneration ongoing (ClinicalTrials.gov identifier: NCT02686658) (Querques et al 2015).…”
Section: 1) Clinical Trials Have Shownmentioning
confidence: 99%